Hazard quotient, odd ratio and relative risk: As the methods for assessment of health risks - Thushyanthy, M.; Gunalan, K.; Asanthi, H.B.; Gamage, T.P.D.; Saravanan, S. (Proceedings of Third International Symposium of South Eastern University, 2013)
Aim of the work was to investigate the pollutants level specially Nitrate- N in the groundwater and compare the obtained results with WHO standard. Groundwater sample were collected from sixty wells consists of thirty cancer patients well as case and other thirty as control within 100 m distance from the highly affected three areas of oesophagus and stomach cancer. Questionnaire was used for case – control study. The determined values expressed by hazard quotient indicate that the water pollutants and their concentrations do not exceed unity. Chunnakam was shown the high odds ratio which was greater than one in all the selected three areas. Ingestion with water is the main pathway for nitrates than the vegetables in areas where groundwater with high nitrate content.
Keywords: Hazard Quotient; Odd Ratio; Relative Risk; Health Risks